Features of Organizational Culture and Their Impact on Banking System Performance - Leskaj, Etleva; Lipi, Ilirjan; Ramaj, Rudina (International Journal of Economic Practices and Theories, 2013)
ABSTRACT Culture is recently considered by researchers as one of the important factors that affects the long-term performance of organizations. This article aims at presenting the general cultural features of major banks operating in Vlora Region, and their impact on the performance of these banks. This research paper will aim to analyze whether these cultural profiles are similar to the cultural profile that contributes to the organization high-performance. The paper methodology is based on the combination between primary and secondary research. The paper ends with the conclusions and recommendations. Key word (s): Organizational culture, financial performance, bank sector JEL classification: M14